Hafnium Impurity Defects in Silicon: A Characterization. (16th October 2018) - Mica, I.; Frascaroli, J.; Vangelista, S.; Caniatti, M.; Piagge, R.; Toia, F. F. R.; Juhel, M.; Polignano, M. L.
Abstract : The aim of this work is to characterize the electrical properties of the defects induced by hafnium (Hf) contamination in silicon by means of different experimental techniques. Hf is introduced in silicon by shallow ion implantation at low doses in order to match experimental conditions close to an accidental contamination; moreover annealing is performed in RTP, that allows to maintain the metallic contaminant in solution. During the annealing the most part of Hf atoms segregate at the SiO2 /Si interface, increasing the density of interface states. A detectable part of Hf atoms diffuse through the silicon bulk producing generation and recombination centers and traps for holes and electrons. Eight levels are detected, six in the upper and two in the lower half of the silicon bandgap, respectively. Hf acts differently in p- or n-type substrates: it is more effective as hole trap and as a recombination center in p-type and it de-activates above an implanted dose of 3 × 10 11 cm −2 only in p-type silicon. The accurate determination of Hf-induced defects even at low concentration allows to find and pinpoint possible hafnium contamination affecting electronic devices.